Using Artificial Intelligence Techniques for Analyzing and Predicting Cryptocurrencies Price - Zekkour Ferhat, Ali; Moumen Messaoud, Salem (university of eloued جامعة الوادي, 2023)
The development of financial technology has brought about a new type of asset called cryptocurrency, which presents an exciting opportunity for investment and we can see the trend of cryptocurrency is in continuous increasing. However, predicting the price of cryptocurrency is challenging due to its volatility and dynamic nature. Therefore, and in order to ensure a correct prediction with good accuracy, we have performed in this project a deep analysis on an existing dataset of the most 4 known cryptocurrencies such as Bitcoin, Binance coin, Ethereum, and Ripple to understand the market behavior by applying different machine learning algorithms such as LSTM, and Prophet to predict their short and long term price behavior. Our experimental result reaches a good level of accuracy.Le développement de la technologie financière a engendré un nouveau type d'actif appelé crypto-monnaie, qui présente une opportunité d'investissement passionnante et nous pouvons voir que la tendance de la crypto-monnaie est en augmentation continue. Cependant, prédire le prix de la crypto-monnaie est difficile en raison de sa volatilité et de sa nature dynamique. Par conséquent, et afin d'assurer une prédiction correcte avec une bonne précision, nous avons effectué dans ce projet une analyse approfondie sur un ensemble de données existant des 4 crypto-monnaies les plus connues telles que Bitcoin, Binance coin, Ethereum et Ripple pour comprendre le comportement du marché en utilisant différents algorithmes d'apprentissage automatique comme LSTM et Prophet pour prédire le prix à court et à long terme. Notre résultat expérimental atteint un bon niveau de précision.
mémoer master informatuque
Keywords: Cryptocurrencies, Prediction, Machine Learning, Deep Learning, Time Series.; crypto-monnaie, prédiction, machine learning, deep learning, séries temporelles